KONSELING INDIVIDU DENGAN TEKNIK SELF-MANAGEMENT UNTUK MENGURANGI PERILAKU AGRESIF PADA SANTRI (STUDI KASUS KLIEN “A” YANG MENJADI KORBAN BROKEN HOME) - Zahwa Juhi; Komaruddin; Zhila Jannati (CV. ADIBA AISHA AMIRA, 2023)
Aggressive behavior is an action taken by an individual intentionally to injure or harm another person physically or verbally. This study aims to describe the aggressive behavior of client